PHAGOCYTIC ACTIVITY MACROPHAGE TO Candida albicans - , I Dewa Ayu Ratna Dewanti ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background: . Most infectious diseases found in the mouth (80%) was candidiasis caused by C albicans. Phagocytic activity by macrophage could affect activity innate response. Phagocytic activity of macrophages in oral caity against C. albicans have not been explained yet. This research aimed to explain whether phagocytic activity was found on wistar rats inoculatedto CandidaalbicansMethods : Subjectsof this researchwere 20 male-wistarrats divided into two groups: ControlGroup(KO)consistedof 10 rats that were not given treatment, while Experimental Groups (KP) were 10 rats that were inoculatedby Calbicans.After 21 days, the rats were sacrifiedand thier toungues were cutfor imunohistochemistry analysis. Data obtained will be analyzed using t test. Results : This research showed significant difference (p&lt